2007
DOI: 10.3348/kjr.2007.8.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Alcohol Embolization Adjuvant to Oily Chemoembolization in Advanced Hepatocellular Carcinoma with Arterioportal Shunts

Abstract: ObjectiveTo assess the feasibility and safety of polyvinyl alcohol (PVA) embolization adjuvant to transarterial oily chemoembolization (P-TACE) in advanced hepatocellular carcinoma (HCC) with arterioportal shunts (APS).Materials and MethodsNineteen patients who underwent PVA embolization for APS before a routine chemoembolization (TACE) procedure were retrospectively reviewed. 10 of these 19 patients underwent follow-up TACE or P-TACE after P-TACE (Group A), but nine patients underwent only initial P-TACE beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
2
15
0
1
Order By: Relevance
“…It was also found that marked improvement in APSs at first-time follow-up significantly favored patient survival. The complete or near-complete occlusion of APS can relieve portal venous pressure and reduce the rates of complications associated with portal hypertension (8,10); this was also confirmed by our results regarding the resolution of refractory ascites and upper gastrointestinal bleeding after APS embolization. Conversely, the occlusion of severe APSs can make patients eligible for chemoembolization.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was also found that marked improvement in APSs at first-time follow-up significantly favored patient survival. The complete or near-complete occlusion of APS can relieve portal venous pressure and reduce the rates of complications associated with portal hypertension (8,10); this was also confirmed by our results regarding the resolution of refractory ascites and upper gastrointestinal bleeding after APS embolization. Conversely, the occlusion of severe APSs can make patients eligible for chemoembolization.…”
Section: Discussionsupporting
confidence: 86%
“…The cumulative 0.5-, 1-, and 2-year survival rates were 79%, 50%, and 12%, respectively. Previous comparable studies involving different materials have shown that median survival varied from 129 days to 330 days; cumulative survival rates at 0.5, 1, and 2 years varied from 45% to 78%, from 12% to 49%, and from 7.8% to 25%, respectively (8)(9)(10)24). The present survival data were better than those reported in studies that used coils or gelatin sponge (8,9), and were similar to those reported in a study that used ethanol (9).…”
Section: Discussionmentioning
confidence: 96%
“…Selective embolization with 200-μm polyvinyl alcohol particles (catalog number G09663, Cook Medical) was performed to achieve stasis in the tumor-feeding artery. During the TACE procedure, the existence and classification of arterioportal shunts were confirmed by hepatic angiography [24]. Selective arterioportal shunt embolization [20,24].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…During the TACE procedure, the existence and classification of arterioportal shunts were confirmed by hepatic angiography [24]. Selective arterioportal shunt embolization [20,24]. Post-TACE syndromes were recorded and liver function indexes were checked within 1 week.…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…Worldwide, embolic agents for the treatment of HCC rupture and bleeding typically include iodized oil, gelatin sponge particles, polyvinyl alcohol and stainless steel ring (17,29), and each agent has its advantages and disadvantages. The agents using iodized oil as the primary embolic agent after years of clinical precipitation are used widely, but during the treatment of HCC by TACE, the necrotic rate of tumors is only 0-4.8% (32,33), and it may lead to severe complications, such as pulmonary embolism (34). However, the application of iodized oil embolization agent is considered to be one of the factors that cause tumor rupture (35,36).…”
Section: Discussionmentioning
confidence: 99%